Defamiliarisasi Konsep Gila Dalam Cerpen Gila Oleh Han Gagas - Damay Rahmawati; Maria Wulandari; Astin Leuisia Maysafira (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
Aku as the main character in the short story Si Gila will represent the anxiety of people with mental disorders faced by other characters as a representation of normal people. The established hierarchy of binary opposition to mentally impaired and normal people is deeply rooted in Indonesian society. The binary opposition in question is the assumption that normal people have more human and spiritual values than those with mental disorders. The establishment of this value makes people with mental disorders experience discrimination and rejection in society in Indonesia. Through a short story by Han Gagas, this research aims to show the existence of binary opposition which is contrary to the current values believed by Indonesian society. Using the deconstruction theory put forward by Jacques Derrida which rejects the existence of one value establishment and closes the possibility of other values. This study tries to show another value construction through reading the short story Si Gila by Han Gagas from the perspective of Deconstruction theory. The results of this study show that my condition as a mental disorder sufferer who becomes the main character is also a symbol of the values that are pinned to people with mental disorders after experiencing the fusion of hierarchical boundaries with the defamiliarization of the concept of crazy as a mental disorder. The results of this study are that mental disorders and normalcy are not a binary opposition, but rather a spectrum.